Slab-related metasomatism in the Patagonia backarc lithosphere of the Andean subduction: the Cerro de los Chenques case. - RIVALENTI, Giorgio; MAZZUCCHELLI, Maurizio; ZANETTI A; BERTOTTO G. W; HEMOND C. (2005)
abs. 10.1474, 01-1080.Cerro de los Chenques is a monogenic quaternary volcano containing spinel facies mantle xenoliths and occurring just North of the latitude of the triple point between the Nazca, Antarctic and South America plates. It overlies the subducted Nazca Plate and occurs at the margin of the supposed slab window induced by the impact of the Chile ridge against South America (Ramos and Kay 1992, Tectonophysics 205, 261-282; Gorring et al. 1997, Tectonics 16, 1-17). Xenoliths are anhydrous lherzolites and less frequently harzburgites and dunites having porphyroblastic to granoblastic texture. All the xenoliths contain glass veins that represent infiltration of the host basalts. The interaction of these glasses with the matrix mineral phases resulted in a very large compositional range that overlaps the composition of the glasses often considered as representative of specific, different, metasomatic agents. For this reason the mantle processes and the nature of the metasomatic agent are constrained only on the basis of matrix mantle clinopyroxene. Clinopyroxenes from the lherzolites are predominately LREE–depleted (Cen/Ybn = 0.26 - 0.91), being the occurrence of LREE-enriched (Cen/Ybn = 1.34 - 2.60) composition limited to very few samples (Cen/Ybn = 1.34 - 2.60). Clinopyroxene compositions in harzburgites vary from steadily LREE-enriched (Cen/Ybn = 14.4) to U-shaped, whereas in dunite clinopyroxene has a slightly concave-upward profile, which mimics in the range MREE-HREE (although at a lower concentration level) that observed in lherzolites.All the pyroxenes are enriched in Th, U and La with respect to Nb and Ta. Th and U enrichment and Nb relative depletion increases in the LREE-enriched lherzolites, in the harzburgites and in the dunite. In general, U/Th is > 1. With the exception of harzburgite clinopyroxenes, Zr and Hf are depleted relative to REE. Similarly, Ti usually defines a negative anomaly and its depletion increases in the LREE-enriched lherzolites and harburgites. The clinopyroxene ...